Inhibition of in vitro proliferative responses of human lymphocytes by rimantadine hydrochloride. - Koff, W C (1979)
Rimantadine hydrochloride (alpha-methyl-1-adamantanemethylamine hydrochloride) inhibits the in vitro proliferative response of human peripheral blood lymphocytes to mitogenic and antigenic stimulation. Addition of drug (25 micrograms/ml) at the initiation of 5-day cultures suppressed the responses to phytohemagglutinin, pokeweed mitogen, and concanavalin A by 25, 65, and 90%, respectively. Similarly, responses to streptokinase-streptodornase, tetanus toxoid, and A2/Aichi influenza vaccine were significantly inhibited at concentrations as low as 10 micrograms of rimantadine per ml. Viability studies on 5-day cultures using trypan blue exclusion showed no significant difference between drug-treated and untreated controls. Furthermore, addition of drug on day 3 of 8-day cultures, at a time when the majority of cells had undergone blastogenesis, greatly suppressed the responses to these mitogens. These studies suggest that, in addition to its antiviral action, rimantadine interferes with the generation of cellular immune responses.